Evaluasi Usability Aplikasi Mobile Banking BCA dengan menggunakan Usability Testing dan System Usability Scale (Studi Kasus: BCA Kota Singaraja) - Ayu Made Krisna Dewi; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT Bank Central Asia Tbk launched the BCA mobile application to maximize the use of technology to answer their customer needs and wants, and to be able to compete in the digital era. However, during implementation, customers find it difficult in viewing transactions history, processing transfers to a different bank, and viewing available balance. Also, the user interface is not up-to-date. Therefore, it is necessary to conduct usability evaluation using the task scenario test and the SUS questionnaire. The task scenario testing was conducted to assess aspects of learnability, error, and efficiency, which involved 6 participants aged 18 - 56 who were divided into two groups. The task scenario test on group 1 obtained the results for the learnability of 41.67%, the efficiency of 0.009 goals/sec, and the error of 0.41. In contrast to the participants in group 2, the result for the learnability was 70.8%, the efficiency was 0.02 goals/sec, and the error was 0.16. Meanwhile, the SUS questionnaire which was used to assess the satisfaction obtained 76.38. According to the interpretation of the SUS score, this figure is in the acceptable category. When viewed from the grade scales, BCA mobile is in the 'C' category with a 'Good' rating.